The Inhibitor Protein (IF(1)) of the F(1)F(0)-ATPase Modulates Human Osteosarcoma Cell Bioenergetics - Barbato, Simona (J Biol Chem, 2015)
The bioenergetics of IF(1) transiently silenced cancer cells has been extensively investigated, but the role of IF(1) (the natural inhibitor protein of F(1)F(0)-ATPase) in cancer cell metabolism is still uncertain. To shed light on this issue, we established a method to prepare stably IF(1)-silenced human osteosarcoma clones and explored the bioenergetics of IF(1) null cancer cells. We showed that IF(1)-silenced cells proliferate normally, consume glucose, and release lactate as controls do, and contain a normal steady-state ATP level. However, IF(1)-silenced cells displayed an enhanced steady-state mitochondrial membrane potential and consistently showed a reduced ADP-stimulated respiration rate. In the parental cells (i.e. control cells containing IF(1)) the inhibitor protein was found to be associated with the dimeric form of the ATP synthase complex, therefore we propose that the interaction of IF(1) with the complex either directly, by increasing the catalytic activity of the enzyme, or indirectly, by improving the structure of mitochondrial cristae, can increase the oxidative phosphorylation rate in osteosarcoma cells grown under normoxic conditions.